"Full Justice May Be Done Them": The Case of Bill, Charles, Jupiter, Randolph, et al. v. William A. Carr in a Florida Freedmen's Bureau Court. Issue 2 (21st April 2019) - Newkirk, Zachary
Abstract: Immediately after the Civil War, freedmen and freedwomen faced an uncertain legal landscape, caught between former owners, reactionary state courts, and a still-potent federal military presence. A system of federal Freedmen's Bureau courts provided many freedpeople with a forum to seek justice outside of often-hostile state courts. A remarkably complete set of documents from one Bureau Court in Leon County, Florida, reveals the extent to which freedpeople and local white legal elites used the new federal court for their respective benefits. The case of Bill, Charles, Jupiter, Randolph, et al. v. William A. Carr provides a new analytical framework to consider the post-Civil War legal landscape in the South. Not only were freedpeople eager to appear before these federal tribunals, but Southern white lawyers—facing immense political uncertainty in 1865 and 1866—were willing to practice in Bureau courts. Both groups' legal arguments reflected the most pressing issues of the time: fair contracting and compensation for freedpeoples' labor; the desire for societal order and stability; and competing notions of subjugation over a recently enslaved group versus justice and equality for them. The success of black people in gaining access to the legal system benefited local white communities and especially white professional lawyers through fees, career advancement, and reputation. Meanwhile, the success of white lawyers in forums like the Bureau courts benefited freedmen, presenting them with skilled allies in new judicial spaces where their rights and freedoms could be articulated, defended, and advanced.